Evidence for different, host‐dependent functioning of Rx against both wild‐type and recombinant Pepino mosaic virus. (12th May 2015) - Duff‐Farrier, Celia R. A.; Candresse, Thierry; Bailey, Andy M.; Boonham, Neil; Foster, Gary D.
Summary: The potato Rx gene provides resistance against Pepino mosaic virus (PepMV) in tomato; however, recent work has suggested that the resistance conferred may not be durable. Resistance breaking can probably be attributed to multiple mutations observed to accumulate in the capsid protein (CP) region of resistance‐breaking isolates, but this has not been confirmed through directed manipulation of an infectious PepMV clone. The present work describes the introduction of two specific mutations, A‐T78 and A‐T114, into the coat protein minimal elicitor region of an Rx ‐controlled PepMV isolate of the EU genotype. Enzyme‐linked immunosorbent assay (ELISA) and phenotypic evaluation were conducted in three Rx ‐expressing and wild‐type solanaceous hosts: Nicotiana benthamiana, Nicotiana tabacum and Solanum lycopersicum . Mutation A‐T78 alone was sufficient to confer Rx ‐breaking activity in N. benthamiana and S. lycopersicum, whereas mutation A‐T114 was found to be associated, in most cases, with a secondary A‐D100 mutation to break Rx ‐mediated resistance in S. lycopersicum . These results suggest that the need for a second, fitness‐restoring mutation may be dependent on the PepMV mutant under consideration. Both mutations conferred Rx breaking in S. lycopersicum, whereas neither conferred Rx breaking in N. tabacum and only A‐T78 allowed Rx breaking in N. benthamiana, suggesting that Rx may function in a different manner depending on the genetic background in which it is present.